Foraging of coptotermes curvignathus (Insecta: Isoptera: Rhinotermitidae) and pattern of damage in oil palm on peat in Bintulu Sarawak - Chan, Seow Phan (2012)
Coptotermes curvignathus is a major pest in oil palm plantation planted on peat. The control of the pest was unsatisfactory due to its lifestyle that made the observation on its foraging behaviour difficult. The objectives of this study were to verify the identity of the pest, to determine the tunnelling activity of C. curvignathus towards presence and absence of food source in the laboratory, to detect the presence and absence of C. curvignathus surrounding an infested palm and lastly to investigate the damage pattern and infestation in oil palm. Tunnelling arena with and without food was prepared to compare the distribution of tunnel length and frequency of tunnel initiation in all direction to see whether any directional feeding occurred. Field study using underground baiting station with rubber wood arranged in all direction was set up surrounding an infested palm to detect the presence or absence of C. curvignathus. Infested oil palms were dissected to see the interior damage caused by C. curvignathus, while survey of the infestation rate was carried out to determine its pattern of infestation. Morphological and molecular studies have verified the termite species as C. curvignathus with 99-100% similarity between 2- 403 bp from the reference samples. The initial tunnelling activity of C. curvignathus was random but food oriented. This was due to insignificant distribution of tunnelling activity and tunnel initiation in no food arena but presence of food induced higher tunnelling activity and higher amount of tunnel initiated. Higher tunnel length was found (234.53 mm) in food present arena compared to no food arena (156.00 mm). The distribution of tunnelling activity in food present arena was not uniform as North sector (335.68 mm) possessed significant higher tunnel length than East (176.55 mm), Southwest (212.76 mm), West (185.24 mm) and Northwest (187.15 mm) respectively. Although the distribution of tunnel initiation was random, it was more likely for C. curvignathus to search in North sector as indicated in the present study. The significant difference of tunnel distribution in certain sector was also due to the search behaviour of the termite whenever food source was encountered. Coptotermes curvignathus tend to branch if the primary tunnel managed to encounter food source while long primary tunnel was excavated if no food were discovered. This observation was supported by significant differences in length of exploratory tunnels (1420. 8 mm) compared to secondary tunnels (351.8 mm) in food present arena. In the food absent arena, primary tunnels significantly dominated with tunnel length of 700.7 mm compared to secondary tunnels (280.6 mm). Coptotermes curvignathus was also observed not visiting all available food sources in the arena and thus, skewed the tunnel distribution in certain sector. Field study revealed that C. curvignathus was scattered surrounding an infested palm. It was a dominant termite species in peat as no other termite species was found within a baiting station occupied by C. curvignathus. Similarly to the laboratory observation, not all baiting station was found infested at any one time during the assessment period. Coptotermes curvignathus damaged the oil palm by excavation and eventually chambers were formed inside the trunk. Thin laminae structures were found within these chambers. Each structure had different thickness (0.98-2.27 mm) and shapes (cell height 3.54-8.92 mm, cell width 6.54-16.82 mm). This constructed structure was believed to be its endoecie where alates and nymphs were found. However the availability of thin laminae structure was random among the infested palm. The infestation incidences of oil palm were found to fluctuate throughout the year. Total infestation incidence ranged from 0.02 to 0.11%. Among the infested palms, about 11.7-23.9% had damage through spear region infestation. There was no evidence of basal infestation during the assessment period. The pattern of infestation was not influenced by monthly rainfall since no significant relationship was established. Regular chemical control managed to keep infestation low but the infestation persisted throughout the years in the surveyed plantations.